Long-Term Management of Vascular Access Ports in Nonhuman Primates Used in Preclinical Efficacy and Tolerability Studies. Issue 6 (2nd July 2020) - Mutch, Lucas A.; Klinker, Samuel T.; Janecek, Jody J.; Niewinski, Melanie N.; M. Z. Lee, Rachael; Graham, Melanie L.
Abstract: Vascular access ports (VAPs) are an essential tool for long-term vascular access in preclinical studies and disease modeling in non-human primates (NHPs). We retrospectively reviewed central (inferior vena cava, IVC) and portal VAP implantation with the maintenance at our center from 15 January 2010 to 31 January 2018. In total, 209 VAPs were implanted for long-term drug administration and sampling. Patency was >95% at 6 months and >80% at 1 year for IVC VAPs and >90% at 6 months and >85% at 1 year for portal VAPs. The majority of animals had no complications and access was generally durable with device use ranging up to 7 years. In IVC, VAPs loss of patency occurred in 13% (0.035/100 d), surgical site infection in 2.9% (0.097/100 d), port pocket infection in 2.2% (0.004/100 d), erosion in 2.9%, 0.008/100 d), and mechanical failure in 4.3% (0.012/100 d). In portal, VAPs loss of patency occurred in 11.3% (0.028/100 d) and port pocket infection in 1.4% (0.003/100 d). About 12% of VAPs were removed as a result of complications. This study confirms VAP implant and maintenance is a beneficial and safe practice in NHPs resulting in favorable outcomes. High patency rates and low complication rates are comparable to the clinical setting. In addition to enabling comprehensive data collection, VAPs increase satisfaction and well‐being by minimizing interference with daily routines and fostering cooperation. VAP implantation, together with an effective maintenance regimen and co-operative handling, is a reliable and convenient refined method for drug administration and blood sampling. Keywords: Vascular access port; nonhuman primates; refinement; central vascular access; portal vascular access; surgical technique; experimental surgery; animal model